Secondary Postpartum Hemorrhage Following Cesarean Section (Journal of Shaheed Suhrawardy Medical College, 2018)
Background : Complications of pregnancy and childbirth have always been one of the leading causes of death and disability among women of reproductive age in developing countries .Globally, postpartum haemorrhage is the single most important cause of maternal death, accounting for about 25% of the total and claiming an estimated 1,50,000 lives annually. Among the postpartum hemorrhage, the primary postpartum hemorrhage is more prevalent, but sufferings from secondary postpartum hemorrhage have been emerging. With the rising trend of cesarean section rate, the incidence of secondary postpartum hemorrhage is also rising.Objective: The objectives of this study is to evaluate secondary postpartum hemorrhage cases following cesarean section and vaginal delivery with the aim of reducing the maternal mortality at child bearing age.Methods: This is a cross sectional observational study in the department of Obstetrics and Gynaecology, DMCH , by purposive sampling method. Total 100 cases of secondary PPH were observed during 1st January 2013 to 31 December 2013.Result: In this study, among the cases 67% were following cesarean section and 33% were following vaginal delivery, mean age of the patients were 29 year, parity ranges from 1 to 5. Regarding the outcome of secondary PPH, severe anaemia, anaemic heartfailure, renal failure and DIC were common in cesarean sections along with hazards of massive blood transfusion and jaundice. 7 patients were died in post cesarean cases and 2 died in post vaginal delivery cases. Causes of death were due to hemorrhagic shock & septicemia.Conclusion: In this is study, the rate of secondary PPH is 67% following cesarean section which is very much alarming . The outcome of secondary PPH following cesarean section is worse than vaginal delivery.J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 23-25